Victory : The Reagan Administration's Scret Srategy that Hastened the Collapse of the Soviet Union - Schweizer, Peter (New York The Atlantic Monthly Press, 1994)
Relates the story of a secret strategy, developed in the Reagan White House in early 1982, that hastened the demise of the Soviet Union by undermining the Soviet economy and its dwindling resource base while subverting the Kremlin's hold on its global empire.
Victory tells the story of a secret U.S. strategy developed in the Reagan White House in early 1982 that hastened the demise of the Soviet Union. In this explosive book, Peter Schweizer provides the riveting details of how the Reagan administration undermined the Soviet economy and its dwindling resource base while subverting the Kremlin$1 (Bs hold on its global empire.s
Keywords: United States -- Soviet Union -- Diplomatic relations